The Effect of Webtoon Application on Students’ Reading Skill at Seventh Grade in SMPN 2 Rogojampi Banyuwangi: English - Dwi Nur Hadiyansah; Septiana Wandira; Nurul Ulfi Mabruroh (JOEY: Journal of English Ibrahimy, 2025)
This research investigated the effect of applied webtoon application on students’ seventh-grade reading skills in SMPN 2 Rogojampi Banyuwangi. A quantitative method with a quasi-experimental design was used to conduct this research. The population was 65 students of seventh grade divided into two classes. The samples were taken by Solvin formula, consisting of 28 students in an experimental class (VIIA) and 28 in a control class (VIIB) by simple random sampling. The instrument for collecting data was a pre-test and post-test in the form of 10 questions of blank word test. The test carried out normality, homogeneity, and t-test. The value of descriptive analysis was a rising value in which the mean of the post-test experimental class (85,71) was higher than the post-test control class (77,50). Furthermore, the value of the t-test with sig. (2 tailed) 0,000. In this matter, 0,000 < 0,05. In other words, H0 is rejected and H1 is accepted. It indicates that the score between the experimental and control classes was different after the applied treatment. which means the webtoon application (X) has a significant effect on students’ reading skills (Y) in seventh grade in SMPN 2 Rogojampi Banyuwangi. The result of the research showed that using the webtoon application affected the student’s reading skills.